STRATEGI PEMASARAN PRODUK IKAN CAKALANG ASAP (STUDI KASUS: UKM FROZEN SEAS) - Triyastuti, Meilya Suzan; Ndahawali, Daniel H.; Ondang, Hetty M. P. (Politeknik Kelautan dan Perikanan Karawang, 2021)
ABSTRAKPenelitian ini bertujuan untuk merumuskan strategi pemasaran ikan cakalang asap di UKM Frozen Seas dengan mengidentifikasi faktor internal maupun eksternal di UKM Frozen Seas. Penelitian dilakukan di UKM Frozen seas, Bitung dengan menganalisis faktor internal dan eksternal yang berdampak pada strategi pemasaran ikan cakalang asap. Hasil penelitian menunjukkan bahwa strategi pemasaran yang diperlukan diantaranya kerjasama dengan perusahaan untuk mendapatkan bahan baku dan produk yang berkualitas; diferensiasi pengemasan yg ramah lingkungan, rasa dan harga yg murah; penerapan teknologi pengasapan yang efektif dan efisien terhadap peningkatan kandungan nutrisi ikan; informasi kandungan gizi pada kemasan, menambah pasar dengan kerjasama dengan pihak terkait. ABSTRACTFrozen seas SMEs need the right marketing strategy so that smoked skipjack products can compete in the digital era. This study aims to formulate a marketing strategy for smoked skipjack tuna in Frozen seas UKM by identifying internal and external factors in Frozen seas UKM. The research method used in this research is the descriptive method. The research data were obtained by conducting observations, documentation, and interviews. The research was conducted at UKM Frozen Seas by analyzing internal and external factors that had an impact on the marketing strategy of smoked skipjack tuna. The results show that there is a need for a marketing strategy to optimize product sales and increase profits. Therefore, it is necessary to have a marketing strategy in the SME Frozen Seas which is needed including cooperation with companies to obtain quality raw materials and products; differentiation of environmentally friendly packaging, taste and low price; application of effective and efficient smoking technology to increase the nutritional content of fish; information on nutritional content on the packaging, adding to the market in collaboration with related parties.